Review of research grant allocation to psychosocial studies in diabetes research. Issue 12 (6th October 2016) - Jones, A.; Vallis, M.; Cooke, D.; Pouwer, F.
Abstract: Aims: To estimate and discuss the allocation of diabetes research funds to studies with a psychosocial focus. Methods: Annual reports and funded‐research databases from approximately the last 5 years (if available) were reviewed from the following representative funding organizations, the American Diabetes Association, the Canadian Diabetes Association, Diabetes Australia, Diabetes UK, the Dutch Diabetes Research Foundation and the European Foundation for the Study of Diabetes, in order to estimate the overall proportion of studies allocated research funding that had a psychosocial focus. Results: An estimated mean of 8% of funded studies from our sample were found to have a psychosocial focus. Conclusions: The proportion of funded studies with a psychosocial focus was small, with an estimated mean ratio of 17:1 observed between funded biomedical and psychosocial studies in diabetes research. While several factors may account for this finding, the observation that 90% of funded studies are biomedical may be partly attributable to the methodological orthodoxy of applying biomedical reductionism to understand and treat disease. A more comprehensive and systemic whole‐person approach in diabetes research that resembles more closely the complexity of human beings is needed and may lead to improved care for individuals living with diabetes or at risk of diabetes. What's new?: The allocation of research funds by a representative sample of diabetes research funding organizations was examined to estimate the overall proportion of studies that have a psychosocial focus. An estimated mean of 8% of funded studies in our sample were found to have a psychosocial focus. Biomedical reductionism in diabetes research and the rationale and merits of a more comprehensive and dynamic whole‐person approach are discussed.